Sectoral Differences in Wage Freezes and Wage Cuts: Evidence from a new Firm Survey - Daniel Radowski; Holger Bonin (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The paper provides evidence concerning incidence and sources of nominal wage rigidity in services and manufacturing, using a new and large employer survey on wage and price setting behaviour for Germany. We observe that wage freezes are more frequent in services than in manufacturing, whereas wage cuts are less frequent. The significant sector gaps do not vanish after controlling for relevant firm characteristics influencing the incidence of wage freezes and wage cuts, notably coverage by collective agreements and the degree of price competition on the product market. An analysis of firms' view on the reasons preventing wage cuts suggests that specific fear of excess worker turnover could explain distinct wage setting behaviour in services.
Keywords: J31; L60; M52; 330; Nominal Wage Rigidity; Efficiency Wages; Manufacturing and Services; Germany; Lohnrigidität; Lohnbildung; Dienstleistungssektor; Effizienzlohn; Verarbeitendes Gewerbe; Deutschland